Depresi, Kecemasan, dan Stres Remaja selama Pandemi Covid-19. - Swastika Tiara Pertiwi; Marisa Fransiska Moeliono; Lenny Kendhawati (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2021)
Adolescent are quite vulnerable to experience negative psychological conditions such as depression, anxiety, and stress. The existence of the Covid-19 pandemic has led to policies such as social distancing that restrict adolescent so they need to adapt to be able to carry out their daily activities and carry out their developmental tasks. This study aims to determine the prevalence of negative psychological conditions in adolescent, such as depression, anxiety, and stress during the Covid-19 Pandemic. This research is a quantitative descriptive approach with a cross-sectional design. This research was conducted during August 2020 on 647 adolescents aged 14-18 years in Bandung. The measuring instrument used was the DASS-42 which was done online by participants. The reliability of DASS-42 in this study has an alpha coefficient of 0.955. The results showed that the most negative psychological condition experienced by adolescent during the Covid-19 Pandemic was anxiety, which was found in 58,74% of adolescent. In addition, 32,15% of adolescent experienced depression and 34,7% of adolescent experienced stress during the Covid-19 Pandemic. The prevalence of negative psychological conditions such as depression, anxiety and stress are more experienced by girls than boys.Keywords – Depression, Anxiety, Stress, Adolescent, Covid-19.